Pengaruh Minat Olahraga Terhadap Hasil Belajar PJOK di SDN II Yungyang Modo Lamongan - Juniar Aryanto, Sherif (Universitas Hamzanwadi, 2024)
The lack of interest among students in physical activities in Physical Education, Sports, and Health (PESH), or commonly known as sports, affects the learning outcomes of Physical Education, Sports, and Health in students, as evidenced by the 60% of students who have not completed their learning. Therefore, this research aims to determine the relationship between Sports Interest and Learning Outcomes in PESH at SDN Yungyang II using a quantitative approach method. The research sample is limited to fifth-grade students of SDN Yungyang II using a correlational technique that connects sports interest variables with learning outcomes. Several tests were conducted in this research, namely prerequisite tests and correlation test results. The prerequisite test is a normality test with a result of 0.062 > 0.05, and the sig value on Learning Outcomes is 0.145 > 0.05, indicating that the data is normally distributed. The second test is the linearity test, which obtains a result of 0.296 > 0.05, indicating that the data used in this research is linear. The correlation test result in this research is a sig value of 0.00 < 0.05, which means they are related, with a person correlation value of 0.94 > 0.39, indicating a positive and very strong relationship.